Clinical study on the treatment of chronic heart failure with a novel D‐shant atrium shunt device. (18th February 2022) - Shang, Xiaoke; Liu, Mei; Zhong, Yucheng; Wang, Xueli; Chen, Song; Fu, Xiaojuan; Sun, Ming; Xie, Mingxing; Ke, Yuhe; Guan, Ying; Zhang, Changdong; Dong, Nianguo
Abstract: Background: Atrial septal shunt devices might improve hospitalizations and also prognosis in heart failure with increased pulmonary pressures due to left heart diseases. In recent years, atrial shunt devices have been used for the treatment of chronic heart failure, but there remains a lack of clinical experience. This study aimed to analyse the therapeutic effect of a novel type of atrial shunt on chronic heart failure. Methods and results: From May 2020 to September 2020, six patients who were diagnosed with chronic heart failure and completed percutaneous D‐shant atrium shunt device implantation in the Department of Cardiovascular Surgery, Union Hospital, were retrospectively included. The shunt location was evaluated by echocardiography and digital subtraction angiography. Heart function was evaluated by New York Heart Association functional class. Echocardiography was used to measure the diameter of the new chamber and ventricle, and to evaluate the degree of mitral and tricuspid regurgitation. Before operation and 6 months after operation, left atrial end‐diastolic volume, right atrial end‐diastolic volume, left ventricular end‐diastolic volume, and right ventricular end‐diastolic volume were measured by magnetic resonance imaging. Left ventricular ejection fractions and right ventricular ejection fractions were calculated. Haemodynamic indexes of right heart catheterization and clinical cardiac function indexes were collected and compared before and 6 months after shunt implantation. All six patients completed percutaneous shunt device implantation. Echocardiography and digital subtraction angiography showed that the shunt device was correctly positioned and unobstructed in all patients. Echocardiography revealed that the left ventricular diameter decreased significantly from 6.40 ± 0.57 mm to 5.03 ± 0.73 mm ( P  < 0.05). There was an obvious decrease in mitral regurgitation. Magnetic resonance imaging showed a reduction in the volume of the left ventricle (182.00 ± 27.02 mL vs. 125.75 ± 16.11 mL, P  < 0.05). Cardiac catheter examination showed the mean left atrium pressure or pulmonary capillary wedge pressure decreased postoperatively (31.83 ± 11.55 vs. 18.00 ± 5.51 mmHg, P  < 0.05). There was also obvious improvement in clinical indicators of cardiac function at 6 months after implantation. Conclusions: This novel D‐shant atrium shunt device revealed maintained good function, no dislodgement and no paradoxical emboli. After implantation, functional mitral regurgitation in all patients with heart failure with reduced ejection fraction improved.